The Development of Constitutional Law in Presidential and Vice Presidential Election Disputes: A Comparison Between Indonesia, Algeria, and Ethiopia - Fakhry Amin (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
The development of constitutional law studies necessitates that constitutional law be understood broadly, including various developments in constitutional law in other countries. One important aspect in the development of constitutional law studies is related to disputes over the results of the Presidential and Vice Presidential elections. Many dynamics occur regarding the disputes over the results of the Presidential and Vice Presidential elections. This research focuses on analyzing the comparative legal development of constitutional law related to presidential and vice-presidential election disputes between Indonesia, Algeria, and Ethiopia. This research is a normative legal study with a conceptual, legislative, and comparative legal approach. The research findings affirm that the court is deemed to have the authority to ensure the implementation of principles in elections as part of the general principles in constitutional law, thus the court is also authorized to assess the dimension of justice in disputes over the results of the Presidential and Vice Presidential elections. The legal comparison of the regulation of presidential and vice-presidential election disputes in Indonesia, Algeria, and Ethiopia does not actually have significant differences. In all three countries, elections can also be challenged in court. The main difference lies in the effectiveness of the judicial review of the Presidential and Vice Presidential election results, where this has been quite successful in Indonesia but less impactful in addressing societal polarization as seen in Algeria and Ethiopia.